Hepatocellular Carcinoma Screening and Diagnosis - Sherman, Morris; Colombo, Massimo (Seminars in Liver Disease, 2014)
All the major liver disease societies have recommended screening for hepatocellular carcinoma (HCC). The target population for HCC screening has been defined by cost-efficacy analyses and by risk scores. Risk scores have been developed for patients with hepatitis B, regardless of the presence of cirrhosis, and for other patients with cirrhosis. Screening is with ultrasound; however, in Asia biomarkers are also used. The additional value of biomarkers has not been demonstrated. The ideal screening interval is 6 months; in Japan shorter intervals are used. Screening detects small lesions that require confirmation of HCC. There are radiological criteria that help determine whether a biopsy is necessary. Special stains can determine whether a lesion that closely resembles normal or dysplastic tissue is HCC. All these tools should be used in the management of patients undergoing HCC screening.
Keywords: hepatocellular carcinoma; cost-efficacy analysis; alpha fetoprotein; risk scores